Antidepressant Effect of Thymoquinone in Animal Models of Depression - Aquib, M.; Najmi, A. K.; Akhtar, M. (Drug Research, 2015)
Objective: The present study was carried out to determine the role of thymoquinone (TQ) in modulating the levels of neurotransmitter and reducing the oxidative stress in animal models of depression.Material and Methods: Mice were divided into 5 groups, each group had 6 animals. TQ (20 mg/kg) in corn oil and fluoxetine (10 mg/kg) in normal saline were administered intraperitoneally (i.p.) half an hour before performing behavioural tests. Modified forced swim test (MFST) and tail suspension test (TST) were used to assess the antidepressant effect in mice. Animals were sacrificed and their brains were removed for biochemical estimation after performing behavioural tests.Results: TQ treatment showed increased swimming, climbing and decreased immobility times in MFST and TST. Combination of TQ with fluoxetine in MFST and TST showed potentiating effect in the present study. A significant elevation of 5-hydroxytryptamine (5-HT) levels was observed following TQ administration in the behavioural models studied. MFST and TST reduced glutathione and elevated TBARS levels in mice. Pre-treatment of TQ restored glutathione and decreased TBARS levels. TQ combination with fluoxetine also showed reduction of TBARS and increased glutathione levels.Conclusion: TQ demonstrated antidepressant effects in MFST and TST respectively in the present study. It further demonstrated antioxidant effects by reducing thiobarbituric acid reactive substance (TBARS) and increasing reduced glutathione (GSH) levels. Although our results are preliminary, further investigations may be required however, based on afore mentioned results, it may be suggested that TQ could be a potential candidate for the management of depression.
Keywords: depression; thymoquinone; modified FST; TST